The Relationship Between Namaz Practice, Attachment to God, and Life Values: Exploring Anxious and Avoidant Dimensions - Irshad, Rimsha; Nawaz, Ayesha; Rehman, Aqsa (Al-Amīr Research Journal for Islamic Studies, 2024)
Prayer, specifically namaz is a central tenet of Islamic faith, serving as a means for believers to connect with the Divine and cultivate a deeper spiritual relationship. This study aims to explore the intricate relationship between prayer practices, Attachment to God (Anxious & Avoidant), and Life Values within an Islamic context. This quantitative study used a cross-sectional survey design to examine the relationship between prayer practices and life values among Muslim individuals in Bahawalpur. The study used approved tools to measure research variables and asked questions about prayer routines. For the study, 200 female students selected as a sample. The study identified a significant negative correlation between life values and avoidant and anxious attachment to God, revealing that smaller adherence to life values is linked to higher degrees of these attachment styles. It was shown that avoidant attachment to God had greater impacts on life values than anxious attachment. Additionally, the findings showed no significant differences in life values or attachment to God based on the frequency of namaz, suggesting that regular religious activities have little bearing on these factors. This study has significant implications for the fields of academia and practice. Key Words: Prayer, Namaz, Attachment to God, Avoidant Relationship with God, Anxious Relationship with God Life Values